Hedonistic Behavior and Efforts to Overcome It - Salmi S. Ali (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2021)
This research is a case study with qualitative method aiming to determine (i) hedonistic behavior of student at Senior High School 6 of Palopo, (ii) factors behind the hedonistic behavior of student at Senior High School 6 of Palopo, and (iii) efforts used to overcome hedonistic behavior of student at Senior High School 6 of Palopo. Subject of this research is a twelfthgrade student who is identified as having hedonistic behavior. Interview and observation guidelines were used as instruments of data collection. The data were then analyzed using descriptive analysis with triangulation technique. This study discovered that (i) the subject's description of hedonistic behavior is due to her interests (in branded goods and to be the center of attention), activities (spending a lot of time outside, buying things that are not needed, and visiting shopping centers and cafes), and also opinions (views of life), (ii) hedonistic behavior of the subject was caused by internal and external factors in which the internal factors came from the subject itself such as the desire to be recognized, while the external one was parents’ attention, social environment’s influence, and peers influence, (iii) the effort conducted to overcome the hedonistic behavior was individual counseling with logotherapy technique.